2003
DOI: 10.1590/s0100-204x2003001100011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de escória de alto forno no crescimento radicular e na produtividade de arroz

Abstract: Resumo -A utilização agrícola de resíduos industriais como fertilizantes decorre da necessidade de diminuir o efeito nocivo do acúmulo de nutrientes nos centros de produção. O objetivo deste trabalho foi avaliar os efeitos de escória de alto forno no crescimento radicular e na produtividade do arroz de terras altas irrigado por aspersão. O experimento foi realizado no campo, adotando-se o delineamento experimental de blocos casualizados, com cinco doses de escória de alto forno (0, 2.550, 5.100, 10.200 e 15.30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
1
8
0
5
Order By: Relevance
“…The results presented here are similar to those reported by Rocha et al (2011), who found that the residual effect of silicate tended to enhance the K concentration in sorghum leaves. This result can be a consequence of improved root growth, once Si application enhances root structures, as reported by Carvalho-Pupatto et al (2003). In addition this increase in Ca concentration in the wheat leaves ( Figure 3b) is due to supply of this nutrient with calcium silicate rates.…”
Section: Resultssupporting
confidence: 66%
“…The results presented here are similar to those reported by Rocha et al (2011), who found that the residual effect of silicate tended to enhance the K concentration in sorghum leaves. This result can be a consequence of improved root growth, once Si application enhances root structures, as reported by Carvalho-Pupatto et al (2003). In addition this increase in Ca concentration in the wheat leaves ( Figure 3b) is due to supply of this nutrient with calcium silicate rates.…”
Section: Resultssupporting
confidence: 66%
“…However, they focused on the evaluation of the acidity correction and Ca, Mg, and Si supply under field conditions (BARBOSA FILHO et al, 2001;KORNDÖRFER et al,2001;CARVALHO-PUPPATTO et al,2003) and pots (PEREIRA et al,2004;KORNDORFER et al, 1999;CAMARGO et al, 2007b) and only a few studies (RAMOS et al, 2008) have evaluated the benefits of Si supply for the rice crops on its uptake, yield and quality without the additional effects (increasing on pH and Ca and Mg content in soils) of silicate applied in tropical soils. The Ca and Mg levels in soil had to be used in the same quantities when different silicate rates were applied in soil, as already done in incubation studies of Si sources and rates (CAMARGO et al, 2007a;PEREIRA et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos (Pereira et al, 2004;Carvalho-PuPatto, 2003;Berni e PraBhu, 2003) têm demonstrado que as gramíneas respondem favoravelmente à adubação silicatada, particularmente quando cultivada em solos com baixos teores de Si "disponível".…”
Section: Introductionunclassified